Identification of Maslow's Hierarchy Needs in Patients Undergoing Hemodialysis in The Hemodialysis Room: Scoping Review - Akmal Zaki Asaduddin; Fitri Arofiati (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: Chronic kidney disease is a syndrome of the kidney and a national health problem with significant morbidity and mortality. This disease not only attacks physically but also attacks psychologically. Patients undergoing hemodialysis therapy require actions according to what the patient needs. Method: The journal selection method uses PRISMA using databases at Scopus, Pubmed, ProQuest, and Sciencedirect. Results: A total of 11 studies of 2415 articles were included in this study with 2244 respondents. Most of the research discusses psychological needs (n:8). On the other hand, what is least discussed is the need for belonging and love and the need for self-esteem (n:2). Based on research conducted by previous researchers, patients undergoing hemodialysis have several factors that support the needs of chronic kidney failure patients. Conclusion: The needs of hemodialysis patients can be explained through Maslow's hierarchy theory. This theory suggests that humans have tiered needs, starting from the most basic needs to more complex needs. In this literature, the most widely needed need is physiological needs. So that nurse intervention can meet the needs of hemodialysis patients by paying attention to and meeting the needs at each level of Maslow's hierarchy optimally. Abstrak: Latar belakang: Penyakit ginjal kronis adalah suatu sindrom pada ginjal dan masalah kesehatan nasional dengan morbiditas dan mortalitas yang signifikan. Penyakit ini tidak hanya menyerang secara fisik tetapi juga menyerang secara psikis. Pasien yang menjalani terapi hemodialisis memerlukan tindakan sesuai dengan yang dibutuhkan pasien. Metode: Metode pemilihan jurnal menggunakana PRISMA menggunakan database di Scopus, Pubmed, ProQuest, dan Sciencedirect. Hasil: Sebanyak 11 penelitian dari 2415 artikel dimasukkan dalam penelitian ini dengan 2244 responden. Sebagian besar penelitian membahas kebutuhan psikologis (n:8). Di sisi lain, yang paling sedikit dibahas adalah kebutuhan akan rasa memiliki dan cinta serta kebutuhan akan harga diri (n:2). Berdasarkan penelitian yang dilakukan oleh peneliti sebelumnya, pasien yang menjalani hemodialisa memiliki beberapa faktor yang mendukung kebutuhan pasien gagal ginjal kronik. Kesimpulan: kebutuhan pasien hemodialisis dapat dijelaskan melalui teori hierarki Maslow. Teori ini mengemukakan bahwa manusia memiliki kebutuhan yang berjenjang, mulai dari kebutuhan yang paling dasar hingga kebutuhan yang lebih kompleks. Dalam literatur ini, kebutuhan yang paling banyak dibutuhkan adalah kebutuhan fisiologis. Sehingga intervensi perawat yang dapat membantu memenuhi kebutuhan pasien hemodialisa dengan memperhatikan dan memenuhi kebutuhan pada setiap level hirarki Maslow secara optimal.